2006
DOI: 10.3748/wjg.v12.i15.2363
|View full text |Cite
|
Sign up to set email alerts
|

Biological role of surface Toxoplasma gondii antigen in development of vaccine

Abstract: SAG1 may be an excellent vaccine candidate against T gondii. The immune protection induced by SAG1 against T gondii may be regulated by both hormone- and cell-mediated immune response.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 17 publications
0
13
0
3
Order By: Relevance
“…Furthermore, CLN was proven to trigger apoptosis-like cell death of intracellular parasites (Ni Nyoman and Lüder 2013). Whereas, with NSO, through its strong enhancement of immune cells (T helper 1) counteracts the known strategies employed by Toxoplasma to inhibit T lymphocyte function which in turn leads to T cells unresponsive and exhaustion (Liu et al 2006;Salem et al 2011). Therefore, the effect of NSO +PYR combination on survival rate and tachyzoite counts was comparable to that of CLN+PYR (Rodrigues et al 2014).…”
Section: Discussionmentioning
confidence: 73%
“…Furthermore, CLN was proven to trigger apoptosis-like cell death of intracellular parasites (Ni Nyoman and Lüder 2013). Whereas, with NSO, through its strong enhancement of immune cells (T helper 1) counteracts the known strategies employed by Toxoplasma to inhibit T lymphocyte function which in turn leads to T cells unresponsive and exhaustion (Liu et al 2006;Salem et al 2011). Therefore, the effect of NSO +PYR combination on survival rate and tachyzoite counts was comparable to that of CLN+PYR (Rodrigues et al 2014).…”
Section: Discussionmentioning
confidence: 73%
“…IFN-γ plays a leading role in restricting both acute phase tachyzoite breeding and chronic phase bradyzoite activation in the cysts. Studies have shown that good DNA vaccines tend to stimulate a Th1-type rather than a Th2-type immune response [8, 33]. The Th2 cytokines IL-4 and IL-10 limit the differentiation of CD4+ T cell to Th1, thereby decreasing the level of IFN-γ [34, 35].…”
Section: Discussionmentioning
confidence: 99%
“…DNA vaccines induce a persistent and strongly protective immune response [6, 7]. For example, T. gondii surface antigen 1 (SAG1) induces effective and durable humoral and cellular immune responses in immunized mice and is regarded as a standard compared to other antigens [8]. …”
Section: Introductionmentioning
confidence: 99%
“…Passive immunization of mice with anti-SAG1 antibody following challenge with a lethal dose of tachyzoites significantly increased survival compared to mice treated with control ascites (7). T. gondii tachyzoites treated with mouse monoclonal antibodies to SAG1 are reported to be gathered together, destroyed, deformed, and swollen, with the formation of holes and gaps on the surface (21).…”
Section: Discussionmentioning
confidence: 99%